Mean platelet volume in the differential diagnosis of tuberculous and bacterial meningitis - Camara Lemarroy, Carlos Rodrigo; Delgado García, Guillermo Rubén; De la Cruz González, Juan Gilberto; Villarreal Velázquez, Héctor Jorge; Góngora Rivera, Juan Fernando (2016)
Abstract Introduction: Mean platelet volume (MPV) has been shown to reflect the inflammatory burden in different inflammatory and autoimmune diseases. Our objective was to analyze the MPV in patients with tuberculous (TBM) and bacterial meningitis (BM). Methodology: The demographic and clinical data of 73 consecutive patients that presented with either BM (n = 35) or TBM (n = 38) were retrospectively analyzed, as well as that of 28 age- and sex-matched controls. Results: MPV was 8.78 ± 1.58 fL in patients with BM and 6.42 ± 1.39 fL in the TBM group (p < 0.05). In the control group, MPV was 7.4 ± 0.66 fL, significantly higher and lower when compared with TBM and BM, respectively. MPV was significantly associated with diagnosis (adjusted OR: 5.15, 95% CI: 1.090–23.7; p = 0.03). With the optimal cut-off value of 7.62 fL, MPV had 82% sensibility and 78% specificity for the differential diagnosis of TBM versus BM. Lower platelet counts, higher serum creatinine, higher white blood cell counts, and higher blood-cerebrospinal fluid glucose ratio were also predictive of BM. Conclusions: Platelet counts were lower and MPV was higher in patients with BM compared to patients with TBM. Platelet indices, available in routine bloodwork, could be useful in the early differential diagnosis of these entities.